Propuesta de un plan de mercadeo para el club especializado en adulto mayor “Otoño Índigo” en San Ramón, Alajuela, Costa Rica - Esquivel-González, Carlos; Barquero-Vega, José Pablo; Alfaro-Rojas, Karen; Salazar-Cartín, Kemberly (Instituto Tecnológico de Costa Rica, 2017)
The business of specialized products and services for the senior adult population is only beginning to become relevant in Costa Rica. Given the identification of the need in the market, the scope of the project was defined, which constitutes a proposal of a marketing plan based on the concept of "Retailing mix" for a club specializing in senior adults in San Ramón, Alajuela, Costa Rica. It is determined with the “Focus group” that the population demands quality products and services, and that there is no offer to meet these needs. With the convenience survey, it is identified that the proposal for the senior adult will have a good acceptance, 88% of the people surveyed would be interested in acquiring the membership. The technical study defines the main aspects to take into account to start the project, determines with the analysis of the large environment and the nearby environment that the risk of implementing it is low, factors related to macrolocalization allows to determine that San Ramón would not be the zone of greater attraction like point of locality but for convenience of the investor the project would initiate in that canton. The description of the business concept is made as a membership club with a "Counter" or "Hospitality desk", as well as the main elements for its strategy. Based on previous studies, the marketing plan was designed for sales, marketing or promotion and utility purposes. It was determined that the project is financially profitable.
Proyecto de Graduación (Maestría en Administración de Empresas) Instituto Tecnológico de Costa Rica. Escuela de Administración de Empresas, 2017.
Keywords: Mercadeo; Asilo de ancianos; Adulto mayor; Nicho de Mercado; Orientación del mercado